(untitled) (Journal of Teleological Science, 2026)
This article seeks to understand the analysis of political totalitarianism developed by the German philosopher, Ernst Cassirer, in The Myth of the State, not in isolation, but as the result of a broader theoretical trajectory, matured throughout his writings on themes related to those developed in his posthumous work. The book is thus situated within a more comprehensive philosophical project aimed at defending rationality and freedom in the face of the political threats of the twentieth century. The objective is to elucidate the meaning of myth in Cassirer’s thought: its function in primitive societies, the role it plays in human experience, and its place within the broader set of cultural forms; as well as the regressive process undergone by social organization, which, having evolved from a mythical matrix toward rational forms of ordering collective life, was nevertheless able to undergo an abrupt inflection marked by the return of myth to the center of political life. Finally, the article analyzes the three fundamental elements that, according to Cassirer, constitute the sophisticated technique responsible for the return of myth as an instrument of political domination: the systematic manipulation of language; the organization of new rituals; and the selection of a leader who embodies collective desire.